(untitled) (American Journal of Islam and Society, 1993)
This small book-Islam as an Alternative-by the German ambassador to Morocco, which contains an excellent foreword by Annemaria e Schimmel, is remarkable for various reasons. Public interest had alwady been heightened due to an earlier television interview with the author which, conducted in a very provocative manner, threw his continued diplomatic appointment into question. However, as German attention turned elsewhere, this issue declined in importance, making it possible for this very eloquent new Muslim to continue representing his country abroad. Events in the Muslim world, such as the Iranian revolution and the Gulf war, often result in many misrepresentations of Islam in the Western media. But these same events also engender a never-ending series of invitations for religious dialogue by people of good will who are trying to understand what is happening and why Islam seems to spread despite its mainly negative image in the eyes of non-Muslims. However, Muslims face a problem here: there are few competent dialogue partners who can present accurately the Islamic side. While representatives of the Catholic and Protestant churches are efficiently trained and very well educated, Muslims in Germany are often unable to express fully and coherently their thoughts in German. They also usually have not received a proper Islamic education. Even if they enroll in a German university specifically for the purpose of acquiring such an education, they are nonetheless tmined to look at their religion through non-Muslim eyes. And it is these very eyes that most often see Islam as “fundamentalist.,“ ”belligerent,” and “backward, particularly as far as women are concerned,” to name only the most important misconceptions. Hoffmann’s book is remarkable because it deals with many controversial issues head on, thereby providing handy answers and explanations for those involved in interfaith dialogue. Many new Muslims may have thought along the same lines in these matters, but to be able to present them in a few and absolutely to-the-point replies is another thing. Here are some of these reizworte (emotive words), in an abbreviated form, together with what the author has to say about them. Fundamentalism: “Each and every religion or ideology develops on some basics-called Bible, Gospel or ‘Marx, Engels, and Lenin’-which are considered definable, concluded, unchangeable and able to support, that is as fundamentals. The same is true of Islam, the fundamentals of which are the ...